Man Ray - em Paris = Man Ray - in Paris - Ray, Man 1890-1976; L'Écotais, Emmanuelle de 1968-; L'Écotais, Emmanuelle de 1968- (Museu Oscar Niemeyer, 2020)
The first exhibition in Brazil of photographer, painter, sculptor and filmmaker Man Ray (pseud. of Emmanuel Radnitzky, United States 1890 - Paris, 1976), one of the greatest visual artists of the early 20th century and one of the most important exponents of the surrealist movement. The 255 works exhibited are objects, videos, photographs and screen printing of varying sizes, developed during the years in which he lived in Paris between 1921 and 1940, his period of greatest creative effervescence. Man Ray arrived in Paris in 1921 full of creative energy. Inspired by Marcel Duchamps readymadesʺ -mundane objects that became works of art in the gallery context-, where he began to experiment with cameraless photography and devised his Rayographs, abstract images produced by placing objects directly on photographic paper and exposing them to light. In 1940 Man Ray returns to the United States and goes on to photograph celebrities from film and fashion. After the end of World War II, Ray returns to Europe and obtains recognition for his work until 1976, the year of the artist's death in Paris.
Keywords: Ray, Man -- 1890-1976; Fotografie; Man Ray / 1890-1976 / Exhibitions; Portrait photography / Exhibitions; Photography, Artistic / Exhibitions; Photography / France / Paris / Exhibitions; Man Ray / 1890-1976; Photography; Photography, Artistic; Portrait photography; France / Paris; Exhibition catalogs; Ausstellungskatalog -- Banco do Brasil, Centro Cultural São Paulo -- 21.08.2019-28.10.2019 -- São Paulo; Ausstellungskatalog -- Banco do Brasil, Centro Cultural Belo Horizonte -- 11.12.2019-17.02.2020 -- Belo Horizonte; Ausstellungskatalog -- Museu Oscar Niemeyer -- 12.03.2020-31.05.2020 -- Curitiba; Bildband